Characterization of Anti-p54 Monoclonal Antibodies and Their Potential Use for African Swine Fever Virus Diagnosis - Tesfagaber, Weldu (Pathogens, 2021)
African swine fever (ASF) is a highly lethal hemorrhagic viral disease of domestic pigs caused by African swine fever virus (ASFV). Although a good advance has been made to understand the virus, a safe and effective vaccine against ASFV is still lacking and its eradication solely depends on its early and accurate diagnosis. Thus, improving the available diagnostic assays and adding some validated techniques are useful for a range of serological investigations. The aim of this study was to produce and characterize p54 monoclonal antibodies with an ultimate goal of developing a monoclonal antibody-based enzyme-linked immunosorbent assay (ELISA) for ASFV antibody detection. Five monoclonal antibodies against p54 protein expressed in Escherichia coli was generated and their characterizations were investigated. Furthermore, a competitive enzyme-linked immunosorbent assay (cELISA) based on a monoclonal antibody designated as 2A7 was developed. To evaluate the performance of the assay, a total of 365 pig serum samples (178 negative and 187 positive samples) were tested and a receiver-operating characteristic (ROC) analysis was applied to determine the cut-off value. Based on the ROC analysis, the area under the curve (AUC) was 0.982 (95% confidence interval: 96.9% to 99.4%), besides a sensitivity of 92.5% and a specificity of 98.9% was achieved when the percent inhibition of 20% was selected as a threshold. Moreover, the result showed an excellent agreement when compared to other commercially available blocking ELISA (kappa value = 0.912) and showed no reaction to other swine pathogens. Overall, the newly developed cELISA method offers a promising approach for a rapid and convenient ASFV serodiagnosis, which could be used as alternative to other serological assays for screening possible ASFV infection.